Citizens’ Political Freedom in Regional Elections after Constitutional Court Decision - Muhammad Azhari Aqil; Ahmad Ahmad; Selvi Aulia Herawati; Diah Puspita Anggraini; Mokhamad Bakhtiar Azami; Rijal Ibnu Sani (Indonesian Journal of Law and Policy Studies, 2023)
Indonesia adopts a democratic system, one indicator of which is reflected in the implementation of Regional Head Elections. In the Regional Head Elections process, a nomination threshold (electoral threshold) had previously been stipulated under Article 40 of Law Number 10 of 2016. However, through Constitutional Court Decision Number 60/PUU-XXII/2024, this provision was amended, reducing the nomination threshold through political parties from the previous requirement of 20% of DPRD seats or 25% of valid votes to a range of 6.5% to 10% of valid votes. This research employs a normative juridical method with a statutory approach. It aims to analyze the extent of citizens’ political freedom in participating in Regional Head Elections and to examine the constitutional implications of the Constitutional Court’s decision for citizens’ political rights and the strengthening of democracy at the local level. The decision opens wider opportunities for political participation through political parties and has the potential to reinforce local democracy in Indonesia.